On relationship abstraction and concretization in assimilation of grammar - Garbačiauskienė, M.; Pajarskaitė, J. (Psichologija, 1966)
Many authors who study the psychological features of grammar assimilation state that lexical and specific word meaning impedes the assimilation of grammatical meaning. The article attempts to show that this happens only when the first meaning is assimilated inaccurately and too narrowly. Correctly assimilated objective word meaning and primary lexical abstractions are necessary for secondary grammatical abstractions.This conclusion is made based on the study of assimilation of noun meaning. The results of experiment showed that it is possible to distinguish two stages of abstraction, based on concretization, in assimilation of noun meaning. In the first stage, the concrete feature of a noun is abstracted and notes the object features that are recognized by sensory organs. In the second stage, the subject begins to understand that one an object is all that includes the system of some features, and thus the noun term includes also abstract nouns.Since difficulties that arise in assimilation of abstract nouns are related with understanding the meaning of nouns, it is important to go deeper into their meaning, which can help more than just focusing on formal features.
Keywords: thinking; thought operations; abstraction; concretization; learning of grammar